2013
DOI: 10.1159/000355734
|View full text |Cite
|
Sign up to set email alerts
|

Adult Renal Size is Not a Suitable Marker for Nephron Numbers: An Individual Patient Data Meta-Analysis

Abstract: Background: Renal size is often used as a marker for nephron numbers as estimation of glomerular numbers is not yet possible in vivo. However, the validity of an association between the two is questionable. As a proper marker for nephron number in an individual is needed in clinical practice, this study was designed to assess the association between renal size and nephron numbers. Methods: An individual patient data meta-analysis was performed on data retrieved with a PubMed and Embase search. Only studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Nevertheless, the observed decrease in right kidney nephron numbers did not affect relative right kidney weight compared with the NF animals. This shows that kidney weight is a poor predictor for nephron number, an observation that was made previously by our group by analyzing human data (Bueters et al, ). In the end, although extrauterine growth restriction itself impairs kidney development, we did not find evidence that it modulated a potential toxicity response of gentamicin or ceftazidime treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, the observed decrease in right kidney nephron numbers did not affect relative right kidney weight compared with the NF animals. This shows that kidney weight is a poor predictor for nephron number, an observation that was made previously by our group by analyzing human data (Bueters et al, ). In the end, although extrauterine growth restriction itself impairs kidney development, we did not find evidence that it modulated a potential toxicity response of gentamicin or ceftazidime treatment.…”
Section: Discussionsupporting
confidence: 77%
“…37 A subject-level meta-analysis of 190 adults (mean age, 51 years) demonstrated that the number of nephrons augments with kidney weight (r=0.17; P=0.03). 38 In our current study, we assumed that renal length reflected the number of nephrons. Even after adjustment for sex, age, and body height, kidney length was still 0.15 cm smaller in cases than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Nephron numbers have been shown to correlate with kidney weight, so renal mass has also been used as a surrogate marker for nephron numbers, although this relationship may be confounded by renal hypertrophy [51,68,69]. In all studies, glomerular numbers correlate inversely with glomerular volume, largely independent of gender and race, potentially reflecting compensatory glomerular hyperfiltration [55,61,70].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%